A cross-border seroprevalence study on HBV, HCV, HDV and HIV in remote Amazonian communities on the border between French Guiana and Suriname - Roxane Schaub; M. Sigrid MacDonald–Ottevanger; Stella Hoang; Amandine Pisoni; Karine Bolloré; Barbara Biche; Anfernee Neus; Rikesh Bisnajak; Janke Schinkel; Julie Blanc; Antoon Grunberg; Richard Naldjinan; et al. (PLoS ONE, 2026)
Background National epidemiological data are essential to achieve viral hepatitis elimination goals. However, viral hepatitis and HIV epidemiology in French Guiana (FG) and Suriname is mainly limited to urban areas. We therefore assessed the prevalence, associated determinants, and knowledge, attitudes, practices, and beliefs (KAP-B) regarding hepatitis B (HBV), hepatitis C (HCV), hepatitis D (HDV), and HIV in the isolated area of the Maroni River, bordering FG and Suriname. Methods Between January 2018 and February 2019, adults (≥18 years) living along the Maroni were enrolled in this cross-sectional study and completed a risk factor and KAP-B questionnaire. Participants were tested for viral hepatitis and HIV using serological and molecular analyses: HBV (HBsAg, anti-HBcore antibodies, anti-HBs, HBV DNA), HCV (HCV-antibodies, HCV RNA), HDV (HDV-antibodies), and HIV (HIV-antibodies/antigen, HIV RNA). Age- and sex-adjusted HBV, HCV, and HIV prevalences were estimated using post-stratification weighting. Findings Among 2286 participants, adjusted prevalences were respectively 2.08% (95%CI: 1.49–2.66; n = 46) for HBsAg, 25.6%, (95%CI: 20.89–29.24, n = 646) for resolved HBV infection (negative HBsAg and positive anti-HBcore antibodies), 0.13% (95%CI: 0.0–0.27; n = 5) for HCV-antibodies, and 0.65% (95%CI: 0.0–1.40; n = 12) for HIV-antibodies. There were no HDV infections. HBV exposure (acute or resolved) was independently associated with age (per 10-year increase aOR:1.27, 95%CI: 1.18–1.37, p < 0.0001), males (aOR:1.34, 95%CI: 1.10–1.65, p = 0.006), Maroon (aOR:2.22, 95%CI: 1.27–4.06) or other ethnic groups (aOR:2.94, 95%CI: 1.61–5.59) versus Amerindians, (p = 0.002), and higher education (aOR:0.71, 95%CI: 0.56–0.90, p = 0.005). Older age (per 10-years increase aOR:1.64, 95%CI: 1.11–2.44), p = 0.01) and non-autochthonous origin (aOR:3.81, 95%CI: 1.14–12.26, p = 0.02) were associated with HIV. Less than one in six participants correctly identified viral hepatitis transmission modes. Conclusion HBV, HCV and HIV prevalences along the Maroni River were comparable to urban areas and remain concerning. Knowledge about viral hepatitis was low. Achieving viral hepatitis elimination goals requires awareness campaigns and test-and-treat strategies tailored to hard-to-serve populations.